2021
DOI: 10.1002/fsn3.2394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Miao sour soup on hyperlipidemia in high‐fat diet‐induced obese rats via the AMPK signaling pathway

Abstract: Obesity is one of the greatest challenges to public health (Aleem et al., 2015). Hyperlipidemia, which mainly manifests as an abnormal increase in serum lipid and/or lipoprotein content (Guo et al., 2018), is a major complication of obesity (Heymsfield & Wadden, 2017). It is usually caused by an unhealthy lifestyle and diet . Recently, due to an increase in the consumption of animal meat, which contains a large amount of energy, saturated fatty acids, and sterols, the risk of obesity and hyperlipidemia has inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
11
1
Order By: Relevance
“…The high-dose group of RTPs could increase the content of HDL-C and significantly reduce the content of LDL-C in mice. As well known, serum TC, TG, LDL-C, and HDL-C levels are key indicators for evaluating lipid metabolism in hyperlipidemia model caused by obesity [ 26 ]. Due to abnormal adipocyte differentiation and the imbalance of lipogenesis and lipolysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high-dose group of RTPs could increase the content of HDL-C and significantly reduce the content of LDL-C in mice. As well known, serum TC, TG, LDL-C, and HDL-C levels are key indicators for evaluating lipid metabolism in hyperlipidemia model caused by obesity [ 26 ]. Due to abnormal adipocyte differentiation and the imbalance of lipogenesis and lipolysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The normal diet and the high-fat were provided by the Animal Center of Guizhou Medical University, and the high-fat diet consisted of 78.8% normal diet, 1% cholesterol, 10% lard, 10% egg yolk powder, and 0.2% bile salt. According to the dietary intake survey, the common dose of MSS is about 10 g/500 mL for adults, and the equivalent dose for rats and humans was converted to determine the MSS intervention dose of 8 g/kg BW per day for this study (Conversion multiplier for 200 g rat to human is 0.16 times) ( 4 ). After the start of the intervention, 50 SD rats were stratified by body weight and divided into five groups by random number method as follows ( n = 10 per group): ND, NDS group were normal diet; HFD, HFDS, HFDIS group were high-fat diet.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization reported that obesity is the leading cause of disability and death in many parts of the world and that a sustainable approach to effective obesity prevention is a more affordable strategy from 10.3389/fnut.2022.1019205 a public health perspective (3). Miao Sour Soup (MSS) is a common food with many years of history of consumption in the minority region of Qiandongnan, Guizhou Province, and is a fermented product made from tomatoes and red peppers after two fermentations (4). Previous research found that MSS contains citral, limonene, α-pinene, β-pinene, ethyl linoleate, ethyl linolenic acid, and other flavor components, but also contains lycopene and capsaicin and other bioactive ingredients (5).…”
Section: Introductionmentioning
confidence: 99%
“…Besides metabolites such as lactic acid and ethanol, many volatile metabolites such as alcohols, esters, and alkenes are also produced [61,62]. A total of 95 volatile flavor substances were detected (Table S1), including hydrocarbons (34), alcohols (26), esters (18), ketones (8), phenols (3), acids (2), and others (4). Figure 2a shows a clustered heatmap of fermentations by different strains, with red (blue) representing larger (smaller) values.…”
Section: Pca Of the Volatile Substances Of Hstmentioning
confidence: 99%
“…He et al [16] studied the effects of thermal and non-thermal processing technology on the quality of HST after storage. Some researchers also investigated the potential role of sour soup in preventing and treating hyperlipidemia, which can reduce the formation of liver fat in the high-fat diet group [17,18]. In addition, the effect of the bacterial community on the volatile flavor profile and the correlation between dominant bacteria and primary metabolites were reported [8,19].…”
Section: Introductionmentioning
confidence: 99%